"Patching up Virtue". Issue 4 (10th October 2013) - Foster, James J. S.
Abstract Herdt's Putting On Virtue has two chief aims. The first is to champion the virtue tradition against Christian moral quietism and modern deontological ethics. The second is to facilitate reconciliation between Augustinian and Emersonian virtue. To accomplish these tasks Herdt constructs a counter‐narrative to Schneewind's Invention of Autonomy, in which Luther's resignation and Kant's innovation are tragic consequences of "hyper‐Augustinianism"—a competitive conception of divine and human agency, which leads to excessive suspicion of acquired virtue. This review argues that Putting On Virtue succeeds in its first aim but leaves its second intriguingly uncompleted. Despite this deficiency, however, this essay also argues that Putting On Virtue makes plausible Herdt's audacious suggestion that Augustinian and Emersonian perfectionism may be reconciled by bringing acquired and infused virtue under a single term.